PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN PEMIMPIN SEBAGAI VARIABEL MODERATING PADA UNIVERSITAS ISLAM SUMATERA UTARA - Supriadi Supriadi (Universitas Islam Islam Sumatera Utara, 2018)
In order to achieve satisfactory performance, professional capability is required and it must go through several stages and conditions. Formal education is still inadequate to achieve professional skills, therefore, companies or organizations should work to improve the quality of their employees' performance through training, education and development. In regard to management and leadership system at the Islamic University of North Sumatra it was identified that employess’ performance has not shownthe expected results. Therefore this research was done to see further more on how the training and motivation that organized by the instituions effect to the performance of employees, and to analyzewhether the leaders as moderating variables might strengthen the training and motivation variables on employees’ performance at the Islamic University of North Sumatra. The data collection in this research was conducted through survey approach with quantitative descriptive research type by distributing questionnaires to 46 people. Data analysis method was using multiple linear regression method with data processing through SPSS (Statistical Package for Social Science). The result showed that simultaneously training and work motivation have a positive and significant impact on the performance of employees at the Islamic University of North Sumatra. Partially, training and motivation respectively have a positive and significant impact on the performance of the employees at the Islamic University of North Sumatra. Besides it, the results showed that the training variable was dominat aspect effecting to the performance of employees, whileleaders as moderating variable did not effect to the training and work motivation on employees’ performance. The coefficient of determination (adjusted R square) showed the ability of training and work motivation could explain the variation of employee performance and was strong enough, while the rest was influenced by other variables beyond variables of this study such as work discipline and compensation.